Evaluation Of The Integrated Non-Communicable Disease (Ncd) Health Centre Programme In Coastal Areas Sukamerindu Health Centre Bengkulu City - Gustri Yani; Wulandari Wulandari; Darmawansyah Darmawansyah (Journal of International Public Health, 2026)
Background: Non-communicable diseases (NCDs) are the leading cause of death in Indonesia and continue to pose a challenge to public health. The Integrated Health Promotion Programme for Non-Communicable Diseases (Posbindu PTM) is a government programme aimed at detecting early risk factors for NCDs through screening, education, and routine, integrated community monitoring activities. The objective of this study was to evaluate the implementation of the Posbindu NCD programme in the coastal area of Sukamerindu Health Centre, Bengkulu City, based on input, process, and output aspects. Research Methodology: A qualitative descriptive method was used with a case study approach involving 17 informants, including the health centre director, programme managers, Posbindu cadres, and community members. Data were collected through in-depth interviews, observations, and document reviews, then analysed using data reduction, data presentation, and conclusion-drawing stages.Research Findings: The results indicate that, in terms of inputs, human resources are sufficient, but some cadres have not received specialised training. Funding and infrastructure are adequate, but their utilisation is not yet optimal. From the process aspect, programme planning and implementation are carried out in accordance with procedures, but community participation remains low and monitoring is not yet sustainable. From the output aspect, community participation in Posbindu PTM activities remains low (only 2,750 out of 4,000 targets), although there has been an increase in knowledge about PTM prevention among participants who actively participate in the activities.Recommendations: The researcher recommends that the Sukamerindu Health Centre in Bengkulu City improve cadre training, maximise the use of infrastructure, increase community participation through continuous education, and strengthen monitoring and evaluation to make the Posbindu PTM programme more effective and sustainable.